Developing Student Worksheets based on Problem Based Instruction on Environmental Pollution Material - Sartika, Emilia; Nizkon, Nizkon; Nawawi, Sulton (UIN Fatmawati Sukarno Bengkulu, 2020)
Student worksheets are a learning tool that plays an important role in learning, but in schools have not used student worksheets in learning. This study aims to reveal (1) how the characteristics of student worksheets based on Problem Based Instruction models on environmental pollution material (2) how the feasibility of student worksheets based on Problem Based Instruction models on environmental pollution material (3) how practicality of student worksheets based on Problem Based Instruction models on environmental pollution material. Research refers to the Borg and Gall development model to the seventh stage, namely potential and problems, data collection, product design, design validation, design revision, product testing, product revision. The research instruments used in data collection were interviews, observation, and questionnaires. The data obtained were then analyzed by quantitative descriptive analysis. The characteristics of student worksheets teaching materials developed using the Problem Based Instruction model on environmental pollution materials are arranged systematically, interestingly, and clearly. Students can learn independently; the developed student worksheets does not depend on other media, and students can interact directly with the environment. Based on the feasibility trial student worksheets is in the